INTEGRATION OF SUSTAINABILITY CONCEPTS IN THE ENVIRONMENTAL MANAGEMENT ACCOUNTING SYSTEM OF CILEGON CITY HOSPITAL - Komarudin, Mochamad Fahru (Yayasan Education and Social Center, 2024)
This research aims to investigate the integration of sustainability concepts in the environmental management accounting system of hospitals in Cilegon City. The concept of sustainability plays a key role in bridging the gap between financial goals and environmental goals of organizations. Through qualitative research methods, data was collected through in-depth interviews, participant observation, and analysis of related documents. The research results show that hospitals in Cilegon City have made efforts to integrate the concept of sustainability in their accounting system, including recording and analyzing data related to medical waste management, efficient use of energy, and efforts to reduce greenhouse gas emissions. However, there are challenges such as limited resources and lack of awareness about the concept of sustainability. This research produces a concrete action plan to increase the integration of sustainability concepts in the hospital environmental management accounting system in Cilegon City. Specific steps proposed include developing new policies, improving infrastructure, training staff, and developing more efficient waste management programs. Thus, this research makes a significant contribution to improving hospital environmental performance in a sustainable manner.